2016
DOI: 10.4236/gep.2016.42004
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Analysis of Surface and Groundwater around Talcher Coal Field, District Angul, Odisha, India

Abstract: The present study deals with the water quality of Talcher Area. Sample was collected from Ghats of river Brahmani, tube well and tap water of different colonies in Monsoon and in Post Monsoon. The collected sample was analysed in P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 4 publications
10
9
0
Order By: Relevance
“…The median and maximum value clearly indicated that slightly reducing conditions existed in the sample collected area at a number of sites. Similar DO concentration was also reported by several authors in literature for instance; 4.32-6.83 mgl-1 [11], 4.18-7.4 mgl-1 [12].…”
Section: B Dissolved Oxygensupporting
confidence: 91%
See 3 more Smart Citations
“…The median and maximum value clearly indicated that slightly reducing conditions existed in the sample collected area at a number of sites. Similar DO concentration was also reported by several authors in literature for instance; 4.32-6.83 mgl-1 [11], 4.18-7.4 mgl-1 [12].…”
Section: B Dissolved Oxygensupporting
confidence: 91%
“…The median sulphate concentration is estimated to be 22.5 mgl-1 for post monsoon samples. Similar sulphate concentration also reported in several literatures such as; 1.85-88.00 mgl-1 [7] 50-132 mgl-1 Angul [11] 53-256 mgl-1 1.2-207 mgl-1 in Angul [12].…”
Section: F Nitrate Phosphate and Sulphate Profilesupporting
confidence: 89%
See 2 more Smart Citations
“…Natural sources of hardness are limestones, which are dissolved by percolating rainwater made acidic by carbon dioxide (Madhusmita Sahoo et al, 2016). The principle cations that impart hardness are Ca and Mg ions.…”
Section: Total Hardnessmentioning
confidence: 99%